Adaptação transcultural para a língua portuguesa do Brasil da Resilience at Work Scale (RAW Scale) - Greco, Patricia Bitencourt Toscani (2018)
The following study aimed to carry out the cross-cultural adaptation of the Resilience at Work Scale (RAW Scale) to the Brazilian Portuguese. RAW is an Australian scale to assess resilience at work. There are versions of 25 and 20 items, with seven areas on a seven-point Likert scale. This is a methodological study of cross-cultural adaptation. The cross-cultural adaptation has included conceptual, item, semantics, operational, measurement, and functional equivalence. Translations, synthesis of translations, back translations, consensus of the versions in English, external assessment by the authors of the original version, assessment by the experts committee and pre-tests. The study population were teachers of the Universidade Federal de Santa Maria as well as health professionals (doctors and nurses, dentists, speech therapists, social workers, pharmacists, physical therapists, psychologists, nutritionists, nursing technicians) of the Santa Maria University Hospital. The sample has comprised 526 workers. It has been conducted a data collection through a questionnaire with information on sociodemographic, employment, RAW Scale Brazil, Job Stress Scale, General Health Questionnaire 12 (GHQ-12), Utrecht Engagement Scale for Assessment at Work, and self-efficacy Scale for Occupational Activities. In order to insert data, Epi-info®6.4 was used with independent double typing to check for errors and inconsistencies. Data analysis was through Software R, applying descriptive statistics and multivariate analysis. The final version of RAW Scale Brazil 25 and 20 items was subjected to evaluation of the psychometric properties through confirmatory factor analysis (dimensional validity), composite reliability, Cronbach's alpha, test-retest reliability, and Spearman correlations with other scales of the questionnaire (convergent validity). The ethical principles were taken into account. Minor adjustments had been made in the process of translation and back translation to contemplate the semantic and idiomatic equivalence among the participants; 64.6% were female, with an average age of 43.9 years old, 45.4% were teachers, and 54.6 % of health workers. Confirmatory factor analysis showed factor loadings ≥0.30. Items 3, 9, 11, 13, 16, and 17, and especially item 18 for RAW scale Brazil 20 showed high residues (≥0.60). The scale showed convergent validity through the correlation strong and positive regarding resilience at work, occupational self-efficacy; moderate and positive regarding engagement at work and social support; and moderate and negative regarding psychological demand and psychological welfare. RAW scale between factors has also presented convergent validity through the strong positive correlation with resilience at work, occupational self-efficacy; moderate and positive engagement with work and social support, and moderate and negative with psychological demand and psychological well-being. The RAW Scale Brazil 25 and 20 items presented adequate psychometric properties for this population.